Perusahaan Otomobil Kedua Sdn. Bhd (Perodua) A Case Study - Ahmad Nazri, Alwyn Zuleika (2008)
This case study gives details on Perodua as a whole - the company's background and history, its vision and mission, its organizational structure and functions and its milestones and achievements through out its 15 years. Perodua is the current market leader in the Malaysian automotive industry and is continuously growing to even greater heights.